Calcification in thymomas can predict invasiveness to surrounding organs. Issue 12 (6th May 2021) - Yoshida, Mitsuteru; Kondo, Kazuya; Miyamoto, Naoki; Kawakami, Yukikiyo; Tangoku, Akira
Abstract: Background: Thymomas are the most common type of anterior mediastinal tumors. Calcification is sometimes observed in thymomas using computed tomography (CT), and it is more frequent in invasive thymomas than in noninvasive thymomas. However, the significance of calcification in thymomas remains unknown. This study aimed to evaluate the significance of calcification in thymomas on invasiveness to surrounding organs and investigate the characteristics of thymoma cases with calcification at our institution. Methods: We included thymoma patients treated at our institution between 2000 and 2016, and evaluated their characteristics, including demographics, calcification on CT, histology, Masaoka stage, and myasthenia gravis status. The patients were categorized into calcification (C) and noncalcification (NC) groups. Results: Among 51 included patients, 11 (21.6%) had calcification. A higher proportion of group C patients had World Health Organization histological type B2 and B3 tumors (high‐risk) than type A, AB, and B1 tumors (low‐risk; p = 0.0477). The number of patients with Masaoka stages III and IV were significantly higher in the C group than in the NC group ( p < 0.0001). The C group patients had significantly higher rates of invasion to the mediastinal pleura, pericardium, lung, phrenic nerve, and chest wall and pleural dissemination than the NC group patients. Conclusions: Calcification reflects invasiveness of tumors to surrounding organs and tissues, and may thus predict thymoma stage and histologically high‐risk thymomas. Calcification in thymomas may also predict the pathological stage and help decide therapeutic methods and surgical approaches to treat thymomas based on the calcification status according to CT findings. Abstract : Calcification in thymomas may reflect invasion to surrounding organs; hence, it may be useful for predicting the pathological stage and helping to decide therapeutic methods and surgical approaches to treat thymomas.